ПЕРВИЧНАЯ СУКЦЕССИЯ СООБЩЕСТВ ОБРАСТАНИЯ НА ИСКУССТВЕННЫХ СУБСТРАТАХ В СЕВАСТОПОЛЬСКОЙ БУХТЕ - (:unkn) unknown (My University, 2010)
На основании многолетних наблюдений в обрастании искусственных субстратов показаны различия последовательности, продолжительности и количестве фаз сукцессии в сообществах двух типов.
PRIMARY SUCCESION OF ASSOCIATIONS OF BECOMING OVERGROWN WITH ON ARTIFICIAL SUBSTRATAKH IN SEVASTOPOL BAY
Longterm supervision of fouling communities (in two types) on the artificial substats has been condact. Distinction in the sequence, duration and quantity of succession phases has been showed.
Keywords: обрастание; сообщество; сукцессия